Fertility trends during successive novel infectious disease outbreaks: Zika and COVID-19 in Brazil - Leticia Junqueira Marteleto; Luiz Gustavo Fernandes Sereno; Raquel Zanatta Coutinho; Molly Dondero; Sandra Valongueiro Alves; Ryan Lloyd; Andrew Koepp (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This study aims to estimate fertility trends in Brazil in the 2010s and early 2020s during a period of back-to-back novel infectious disease outbreaks - Zika virus and COVID-19. We use Brazilian Ministry of Health and Association of Civil Registrar data from 2011-2021 to measure general fertility rates at the national and state levels. We also used seasonal ARIMA model to forecast fertility rates by month and state in 2021 and compared these forecasts with observed fertility rates. We find that fertility rates were steady over 2011-2015 with no statistically significant variation, followed by a sharp decline during the Zika outbreak in 2016 followed by a return to pre-Zika levels after the end of the epidemic. Furthermore, to evaluate the effect of the COVID-19 pandemic, we make comparisons with observed and forecast rates from 2020-2021, showing that declines were generally larger for observed than for forecast rates, yet statistically insignificant. We argue that the resurgence of the COVID-19 pandemic in 2021 might lead to further declines, as women might have not had enough time to adjust rebound from either the effects of the Zika epidemic. We also discuss the importance of timely availability of live births data during a public health crisis with immediate consequences for fertility rates.